Testing the Efficacy of ‘Unlearning’, a Mindfulness and Compassion-Based Programme for Cultivating Nonviolence in Teenagers: A Randomised Controlled Trial - Delgado-Suárez, Irene; López-del-Hoyo, Yolanda; García-Campayo, Javier; Pérez-Aranda, Adrián; Modrego-Alarcón, Marta; Beltrán-Ruiz, María; Gascón, Santiago; Montero-Marín, Jesús (Frontiers in Psychology, 2021)
Background: Most programmes developed to reduce aggressive attitudes among teenagers are based on cultivating nonviolence, a construct that has been related to compassion and, more indirectly, mindfulness. This study aims at testing the efficacy of ‘Unlearning’, a mindfulness and compassion-based programme, for reducing aggressive attitudes in adolescents. Method: A sample of 164 students from three high schools in Zaragoza (Spain) participated in the study. They were randomly assigned to 1) ‘Unlearning’, or 2) relaxation programme. Three assessment points were established: baseline, posttreatment, and a 4-month follow-up. The outcome variables were the subscales of the ‘Attitudes Toward Social Aggression Scale’. Mindfulness and compassion were assessed as secondary outcomes. Results: ‘Unlearning’ did not produce changes in the primary outcomes, but significant effects were observed posttreatment in self-compassion; and in the follow-up, in self-compassion and mindfulness. The control group did not experience any change posttreatment, but a significant effect in mindfulness was observed in the follow-up. The intergroup analyses indicated that ‘Unlearning’ improved self-compassion, both posttreatment (t = -2.48, p = .014) and after 4-months (t = -2.03, p =.044), although these results were not statistically significant after correcting for multiple comparisons. Conclusion: ‘Unlearning’ did not produce significant reductions in aggressive attitudes compared to the control group. The low baseline levels may have hindered the efficacy of the interventions. ‘Unlearning’ showed potential to improve self-compassion, which is related to nonviolence, and this may have positive implications for the adolescents. Future interventions should include teachers and families to enhance the effectiveness of the programmes.